A review on the application of sprayed-FRP composites for strengthening of concrete and masonry structures in the construction sector. (1st March 2018) - Parghi, Anant; Alam, M. Shahria
Abstract: Sprayed fiber reinforced polymer (sprayed-FRP) composites applied on masonry or reinforced concrete (RC) structures as an external reinforcement is an effective mean to obtain a higher level of fiber utilization before premature failure. In the existing literature, most of the studies focused on the conventional types of fibers, i.e. glass, carbon, basalt and aramid (Kevlar) FRP wraps for the repair and rehabilitation of structures. However, limited researchers have dedicated to the investigation of sprayed-FRP retrofitted masonry and concrete structures. This paper provides a broad overview of the recent use of sprayed-FRP composites in construction for the strengthening of RC and masonry structures and describes prospect for the possible improvement in technology. The researchers mostly focused on the main characteristics of dissimilar uses of sprayed-FRP rather than probing down to a criticism of the related scientific shape. Based on the comprehensive review, several important conclusions were re-emphasized, and further research needs were identified for retrofitting RC and masonry structures with sprayed-FRP under different loading scenarios. In this review, the collected evidence prepares the advanced investigation of sprayed-FRP strengthening/repairing of RC and masonry structures that are lacking in the design and application process.